2012
DOI: 10.1016/j.ijid.2012.05.347
|View full text |Cite
|
Sign up to set email alerts
|

Invasion kinetics of human endothelial cells by Toxoplasma gondii RH and ME49 strains

Abstract: Background: India reportedly has 70% of the worldwide burden of Visceral Leishmaniasis(VL), with Bihar having 90% of reported cases. With the support of the RMRI, MSF has implemented a VL treatment project in Vaishali district, endemic for Leishmania donovani, using total dose 20mg/Kg liposomal amphotericin-B(L-AmB) as the first-line drug.Methods: Intravenous L-AmB(Ambisome) has been administered in four doses of 5mg/kg/doses to a total dose of 20mg/kg to all patients identified as primary VL over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, both HMEC-1 and HUVECs showed higher number of parasitic vacuoles per cell when infected by ME49 tachyzoites than by RH protozoan, i.e. ~ 30 vs. 20 at 4 hrs, respectively [779]. These differences may also partly be explained by various division rates of intracellular T. gondii tachyzoites documented in vitro in many primary human cells, including endothelial cells (Table 14).…”
Section: T Gondii Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, both HMEC-1 and HUVECs showed higher number of parasitic vacuoles per cell when infected by ME49 tachyzoites than by RH protozoan, i.e. ~ 30 vs. 20 at 4 hrs, respectively [779]. These differences may also partly be explained by various division rates of intracellular T. gondii tachyzoites documented in vitro in many primary human cells, including endothelial cells (Table 14).…”
Section: T Gondii Infectionmentioning
confidence: 97%
“…Canedo-Solares et al [779] demonstrated that invasion of both human microvascular endothelial cells (HMEC-1) and umbilical vein endothelial cells (HUVECs) by T. gondii RH and ME49 strains increased along with time. HMEC-1 cells were more susceptible to infection with the parasite than HUVECs, and ME49 parasites were faster than RH ones and this may be related to their ability to survive out of the cell and to the fact that T. gondii is more invasive during G1-S phase.…”
Section: T Gondii Infectionmentioning
confidence: 99%